Hubungan Riwayat Anemia Kehamilan dengan Kejadian Stunting pada Balita - Pasalina, Putri Engla; Fil Ihsan , Hafiza; Devita , Hendri (Jurnal Kesehatan, 2023)
The prevalence of stunting at children in Indonesia at age 24-59 months is 43% and in children aged 12-23 months it is 41.2%. Stunting prevalence in West Sumatra is also quite high (25.6%). The prevalence of stunted toddlers in Padang City in 2021 is 22.6%. Stunting carries the risk of low intellectual abilities and growth disorders. The aim of this study was to determine the relationship between a history of anemia during pregnancy and the incidence of stunting in toddlers aged 24-59 months. This research is descriptive analytical with a case control design. This research was conducted in the working area of ​​the Air Dingin Health Center, Padang City, from January to March 2022. The population was 1356 people, and the sample size was 50 toddlers (25 controls and 25 cases). Sampling was taken using the consecutive sample technique. Data analysis was carried out bivariately with the chi-square test. The results of this study show that there is a relationship between a history of anemia during pregnancy and the incidence of stunting (p=0.000). The conclusion of this study is that there is a relationship between a history of anemia during pregnancy and the incidence of stunting.